Party Formation, Political Power, and the Capacity for Reform: Comparing Left Parties in Kerala and West Bengal, India - MANALI DESAI (Social Forces, 2001)
This article discusses the concept of "partyformation," that is, the historically evolved links between a party and the civilsociety from which its political power is derived. This concept is developed through an empirical analysis of differences in poverty eradication by leftist parties in thestates ofKerala and West Bengal, India. Theargument is made that the ostensibly common identity ofa Communist party in the two cases conceals different ''partyformations." In Kerala, it evolved as a morepopularparty, with deeper roots in civil society, while in West Bengal it was much weaker. These differences areattributed to thepolitical practices of each party duringthe anticolonial movement, the structural conditions within which each had to function, and the consequent variations in political power